PELATIHAN PEMBUATAN APLIKASI PEMBELAJARAN BERBASIS ANDROID BAGI GURU SMK ISLAM NURUL HIKMAH - Purmadi, Ary; Wibawa, Restu; Muzakir, Muzakir; Fitriani, Farida; Kurniawati, Wiwien (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
The target of this training activity is Nurul Hikmah Islamic Vocational School teachers. From the result of communication with prospective participants and the school principal, there are various problems faced by teachers in developing capacity or competence, especially in the development of technology-based learning media. For this reason, the solution offered is to conduct training and assistance to teachers at Nurul Hikmah Islamic Vocational School regarding knowledge, skills in developing android-based learning media that are appropriate to the subjects being taught. the method of implementing this community service program is carried out in a participatory and gradual manner. This program will provide provisions to teachers in creating simple applications that can be run by students in learning to use smartphones. In this activity there were 20 teachers who participated and they were very enthusiastic about this activity so that the presenters were enthusiastic in delivering the material. The stages carried out in this training are planning, action to evaluation. The results obtained in this activity are Android-based learning products that teachers can use in learning. And 80% of the trainees understand the importance of using Android-based learning